miRNAs as Biomarkers and Possible Therapeutic Strategies in Synovial Sarcoma - Jiang, Shaowei; Hu, Ying; Zhou, Yi; Tang, Guozheng; Cui, Wenxu; Wang, Xinyi; Chen, Bangjie; Hu, Zuhong; Xu, Bing (Frontiers in Pharmacology, 2022)
Synovial sarcoma (SS) is an epithelially differentiated malignant stromal tumor that has the highest incidence in young people and can occur almost anywhere in the body. It is driven by the fusion oncoprotein SS18-SSX1, one of SS18-SSX2 (or, rarely, SS18-SSx4). Micro RNAs (miRNAs) are small, non-coding RNAs that can be isolated from cells, tissues, and body fluids such as serum, plasma, tears, or urine. Involved in post-transcriptional regulation of intracellular gene expression, affecting a variety of biological processes, including development, proliferation, and differentiation. There is increasing evident that miRNAs can be used both as tumor suppressors and as oncogenes that regulate growth and apoptosis. As related reports continue to grow, the clinical diagnostic value of miRNAs is becoming more and more important for its great diagnostic value in many tumor diseases such as hepatocellular carcinoma and breast cancer. Abundance of evidence has demonstrated that micro-RNAs play a significant role in the development and emergence of synovial sarcoma in recent years. Through our review and analysis of the previous literature, we obtained that some miRNAs have significant connections with the occurrence and development of synovial sarcoma and play great roles in synovial sarcoma from diagnosis and treatment to prognosis. For example, serum miR-92b-3p expression levels may represent a novel approach for monitoring tumor dynamics of synovial sarcoma, the upregulation of miR-214 accelerates development of synovial sarcoma via modulation of cytokine gene expression and tumor microenvironment, cooperating with SS18-SSX1, and miR-494.3p functioning as a tumor suppressor probably is related to the regulator CXCR4 although the specific mechanism is also unclear. In addition, miR-17 and miR-9 can act as oncogenes in synovial sarcoma. To show the connections between synovial sarcomas and some miRNAs, this review described the role of miRNAs in synovial sarcoma in detail.